Approach to the Medical Treatment of Epilepsy. Issue 2 (April 2022) - Brigo, Francesco; Marson, Anthony
ABSTRACT: PURPOSE OF REVIEW: This article discusses the use of antiseizure medications in the treatment of focal and generalized epilepsies using an evidence-based approach. RECENT FINDINGS: In recent years, several new antiseizure medications with differing mechanisms of action have been introduced in clinical practice, and their efficacy and safety has been evaluated in randomized controlled clinical trials. Currently, all antiseizure medications can prevent seizure occurrence, but they have no proven disease-modifying or antiepileptogenic effects in humans. The choice of therapy should integrate the best available evidence of efficacy, tolerability, and effectiveness derived from clinical trials with other pharmacologic considerations, the clinical expertise of the treating physicians, and patient values and preferences. After the failure of a first antiseizure medication, inadequate evidence is available to inform policy. An alternative monotherapy (especially if the failure is because of adverse effects) or a dual therapy (especially if failure is because of inadequate seizure control) can be used. SUMMARY: Currently, several antiseizure medications are available for the treatment of focal or generalized epilepsies. They differ in mechanisms of action, frequency of administration, and pharmacologic properties, with a consequent risk of pharmacokinetic interactions. Major unmet needs remain in epilepsy treatment. A substantial proportion of patients with epilepsy continue to experience seizures despite two or more antiseizure medications, with a negative impact on quality of life. Therefore, more antiseizure medications that could provide higher seizure control with good tolerability and that could positively affect the underlying disease are needed.